A resposta dos manguezais de um estuário do sul da Bahia sob influência das mudanças do clima, flutuações do nível do mar e dinâmica dos canais durante o Holoceno - OLIVEIRA, Nêdra Nunes (Universidade Federal do Pará, 2019)
This work integrates palynology, sedimentology, geomorphology and radiocarbon dating, as well as δ13C, δ15N, and C/N from sedimentary organic matter obtained by the description of a core (5,20 m deep) sampled ~8 km from current coastline, 2m above sealevel at Jucuruçu River valley, near the city of Prado, south coast Bahia-Brazil. Based on this core and previously published works, the effects of climate and Relative Sea-level (RSL) changes on Jucuruçu’s mangroves during the Holocene were detailed. Along the studied core two phases were identified and correlated with others sediment cores. The first phase occurred in part of the middle Holocene (7200 - <6950 cal yr BP), developed on a tidal flat colonized by mangrove. It presents a transition from C3 terrestrial plants to marine organic matter upward this phase. On second phase, a fluvial plain developed followed by a mangrove shrinkage and, herbaceous and ferns expansion. At this phase, the biogeochemical data revealed an increased trend to organic matter sourced from freshwater. The integration of palaeoenvironmental data reveals an important RSL rise, which caused a marine incursion inside this river valley and allowed mangroves establishment under a strong estuarine influence, this incursion reached ~23 km upstream during the middle Holocene. The RSL fall at the middle and late Holocene caused a gradual mangrove replacement by mainly herbaceous vegetation associated to freshwater plankton predominance up river, while mangroves and marine algae migrated to the Jucuruçu river mouth. A decrease fluvial discharge during early and middle Holocene most likely favored this mangrove migration pattern and estuarine/marine organic matter spreading upstream. In contrast, probably the mangrove establishment at river mouth up present days was favored by an increase fluvial discharge at late Holocene. Noteworthy is the fact that tidal channels dynamics have controlled mangrove distribution last thousand years. Therefore, this study allowed to identify and to describe the effects of allogenic (caused by climate and RSL change) and autogenic processes (conducted, for example, by channels dynamic).